2017
DOI: 10.1186/s12862-016-0847-1
|View full text |Cite
|
Sign up to set email alerts
|

A combination of long term fragmentation and glacial persistence drove the evolutionary history of the Italian wall lizard Podarcis siculus

Abstract: BackgroundThe current distribution of genetic diversity is the result of a vast array of microevolutionary processes, including short-term demographic and ecological mechanisms and long-term allopatric isolation in response to Quaternary climatic fluctuations. We investigated past processes that drove the population differentiation and spatial genetic distribution of the Italian wall lizard Podarcis siculus by means of sequences of mitochondrial cytb (n = 277 from 115 localities) and nuclear mc1r and β-fibint7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
92
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(100 citation statements)
references
References 96 publications
8
92
0
Order By: Relevance
“…Older species result to be the soricomorph Sorex samniticus and Talpa romana, and the two insular endemics: the bat Plecotus sardus and the soricomorph Crocidura sicula. It should be considered that the southernmost part of Italy, including Sicily and Sardinia, constitute for some xerophilic species a particular favorable area not only during interglacials but even during glacial maxima when a strong sea level decrease occurred (as much as 120-135 m) leading to the increase of the Mediterranean coastal plains and favoring the formation of new suitable habitats with consequent population expansions (Bisconti et al 2011;Senczuk et al 2017). This could have allowed the survival of some old mammal endemic species as well as for other paleoendemic vertebrates across different climatic oscillations in those southern areas of the country.…”
Section: Discussionmentioning
confidence: 99%
“…Older species result to be the soricomorph Sorex samniticus and Talpa romana, and the two insular endemics: the bat Plecotus sardus and the soricomorph Crocidura sicula. It should be considered that the southernmost part of Italy, including Sicily and Sardinia, constitute for some xerophilic species a particular favorable area not only during interglacials but even during glacial maxima when a strong sea level decrease occurred (as much as 120-135 m) leading to the increase of the Mediterranean coastal plains and favoring the formation of new suitable habitats with consequent population expansions (Bisconti et al 2011;Senczuk et al 2017). This could have allowed the survival of some old mammal endemic species as well as for other paleoendemic vertebrates across different climatic oscillations in those southern areas of the country.…”
Section: Discussionmentioning
confidence: 99%
“…The important feature of plant dispersal is that we can notice whether genes are distributed through dispersal of seed or pollen. This distinction allows us to identify whether environmental components, i.e., phonological differences could affect differential fertilization success between populations and biotic dispersal vectors (Sork et al, 2016). Plants have chloroplast which is haploid and non-recombinant that are important for documentation of migration, and history of population structure.…”
Section: Gene Movementsmentioning
confidence: 99%
“…Results indicated that warmer conditions of the last interglacial-induced population contraction. The phylogeography of Podarcis siculus was studied using mitochondrial cyt b, nuclear mc1r and β-fibint 7 genes (Senczuk, Colangelo, De Simone, Aloise, & Castiglia, 2017). The population level historical demography showed a trend constant with glacial expansion and regional determination during the last glacial maximum.…”
Section: Gene Movementsmentioning
confidence: 99%
See 2 more Smart Citations